Asunnot eläkkeiksi?; Turning Housing Equity into Income in Old Age - Niku Määttänen; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2013)
– Elderly people could markedly increase they standard of living by releasing their housing equity. Purchase of a single-payment life annuity would increase the benefits of this release. The tax treatment of these annuities is, however, very strict in Finland, because both yield and capital are taxed without deductibility of premiums. This study describes the wealth structure of households, assesses the options of taxing single-payment life annuities and analyses how launching of these products would influence tax receipts. We recommend that a rate-of-return allowance should be applied, leaving risk-free interest rate and mortality bonus untaxed. We show that adoption of this tax rule is likely to increase tax revenue, since it would reduce tax-preferred housing.
Keywords: H24; G22; 330; Single-payment life annuity; Equity release; Taxation; Leibrente; Einkommensteuer; Finnland